PREDIKSI EROSI DAN PERENCANAAN KONSERVASI TANAH PADA DAERAH ALIRAN SUNGAI JANGA KABUPATEN KARANGASEM, BALI - Jeksen, Julianus; Diara, Wayan; Wiyanti, Wiyanti (AGRICA, 2008)
Erosion prediction on Janga flow river area at Karangasem district used USLE ( Universal Soil Loss Equation ). This research conducted to know the large erosion on Janga flow river area and conservation treatment on unit larger erosion area of permitted erosion to concern on the class of ability area. Based on slope map compilation, used area map and soil variety map on research area was founded L6 unit area. The large erosion predicts on Janga flow river area between 0,829 to 1.109,208 ton/ha/th. Low erosion in area unit 1,3,5,6,7, and 9 located on downstream of the flow river area. Be on the process of erosion on area unit 11 and 13 located on mid-flow river area. High erosion in area unit 14 and 16 located on upper reaches flow river area. Lowest erosion found in area unit 1,3,5,6,7,9,11 and larger erosion of permitted erosion located in area unit 10,13,14,15,and 16 need to soil conservation treatment. Applicable Soil conservation treatment is increasing the density of crops and improve terrace construction and by added used organic substance and cultivation crop